POTENTIAL OF JAVANESE TURMERIC ETHANOL EXTRACT IN INHIBITING STREPTOCOCCUS SANGUINIS AND PORPHYROMONAS GINGIVALIS BIOFILM FORMATION - HUTAURUK, REINA; SUNIARTI, DEWI FATMA; DJOHAN, WIDURINI (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of the current study was to evaluate the potential of Javanese turmeric ethanol extract in the inhibition of the formation of Streptococcus sanguinis and Porphyromonas gingivalis biofilms, individually and in combination. Methods: The concentration of P. gingivalis and S. sanguinis bacteria ranged from 0.5% to 25%. Inhibition assay for biofilm formation was conducted on a 96-well plate using brain heart infusion (BHI) agar enriched with 0.2% sucrose at 37oC for 18 h. After staining with 0.5% crystal violet, the optical density was measured at 490 nm. Results: Javanese turmeric can potentially inhibit the biofilm formation of S. sanguinis (IC50 0.5%, IC90 15%) and P. gingivalis (IC50 15%) on single and dual species (IC50 0.5%, IC90 15%). Conclusion: Javanese turmeric has the potential to inhibit the formation of S. sanguinis and P. gingivalis biofilms.